Determination of Uranium, Radium and Radon concentrations and Radon surface evaporation rate for different slag samples from Al Shuaiba oil refinery in Basrah-Iraq using CR-39 Detector - Gayyim, Huda R. M. Al- (International Journal of Advanced Science and Technology, 2020)
In this work, the concentrations of Uranium(238U), Radium(226Ra), Radon(222Rn) and Radon surface evaporation rate were measured in the samples of slag taken from different places in pipes and tanks for Al-Shuaiba oil refinery in Basra-Iraq. The purpose of this study is to determine whether these measured values are within the internationally permissible limits or not. Sixty samples of slag brought from the different places, 37 from pipes and 23 from tanks in the refinery. CR-39 detector is using in this investigation. Results are showing variation and variance in measured values, where in pipes range from (8.029 ppm to 17.926 ppm), (5.775 Bq.kg-1 to 12.898 Bq.kg-1), (1569.337 Bq.m-3 to 3272.948 Bq.m-3) for concentrations of Uranium, Radium and Radon respectively, and from (0.000544 Bq.m-2.s-1 to 0.00113 Bq.m-2.s-1) for Radon surface evaporation rate. In tanks, the measured values range from (8.351 ppm to 16.252 ppm), (6.007 Bq.kg-1 to 11.69 Bq.kg-1), (1493.807 Bq.m-3 to 2761.026 Bq.m-3) for the concentrations of Uranium, Radium and Radon respectively, and from (0.000517 Bq.m-2.s-1 to 0.000956 Bq.m-2.s-1) for Radon surface evaporation rate. In this study, most of the measured concentrations are high according to (ICRP), and the value of each element above correlated with value of each other's. The presence of slag on the walls of the pipes and tanks of the oil refinery is the source of radiation doses to which workers are exposed. This study is the first investigation provided a database of uranium and the other radiated elements to this refinery.